Modelling of Threat Evaluation for Dynamic Targets Using Bayesian Network Approach. (2016) - Kumar, Sushil; Tripathi, Bipin Kumar
Abstract: Threat evaluation is an uncertainty process to protect the assets against the various enemy targets such as aircrafts, missiles, helicopters etcetera. There is one critical thing in threat evaluation of targets is threat level or degree of threat which depends upon the enemy targets and their change in behaviors at instant, because each target has individual behavior. Analysis of individual behavior of the target is difficult task. So there are various parameters come into the picture which are extracted from multiple sensors are involved for evaluation of threat level of target to improve situational awareness and decision making. Threat level evaluation is complex task because of uncertainty involved in the process. In uncertainty case involved in threat evaluation process, Bayesian Network has great deal to overcome uncertainty in the model.